New cancer cases in France in 2015 attributable to different levels of alcohol consumption. (29th September 2017) - Shield, Kevin D.; Marant Micallef, Claire; Hill, Catherine; Touvier, Mathilde; Arwidson, Pierre; Bonaldi, Christophe; Ferrari, Pietro; Bray, Freddie; Soerjomataram, Isabelle
Abstract: Background and aims: Alcohol consumption increases the risk of cancer. Thus, to inform policy decisions, this study estimated the number of new cancer cases in France in 2015 attributable to alcohol consumption generally and to light (< 20 g per day (g/day) among women; < 40 g/day among men), moderate (20 to < 40 g/day among women; 40 to < 60 g/day among men) and heavy drinking (≥ 40 g/day among women; ≥ 60 g/day among men), and the number of cancer cases that would have been prevented assuming a previous 10% decrease in alcohol consumption. Design: New cancer cases attributable to alcohol were estimated using a population‐attributable fraction methodology, assuming a 10‐year latency period between exposure and diagnosis. Setting and participants: Population of France, 2015. Measurements: Alcohol consumption was estimated by coordinating data from the Baromètre santé 2005, a national representative survey ( n = 30 455), with data from the Global Information System on Alcohol and Health. Relative risks were obtained from meta‐analyses. Cancer data were estimated based on data from the French Cancer Registries Network. Uncertainty intervals (UI) were estimated using a Monte Carlo procedure. Findings: In France in 2015, an estimated 27 894 (95% UI = 24 287–30 996) or 7.9% of all new cancer cases were attributable to alcohol. The number of alcohol‐attributable new cancer cases was similar for both men and women, with oesophageal squamous cell carcinomas having the largest attributable fraction (57.7%). Light, moderate, heavy and former alcohol drinking were responsible for 1.5, 1.3, 4.4 and 0.6% of all new cancer cases, respectively. Lastly, if there had been a previous 10% reduction in alcohol consumption, 2178 (95% UI = 1687–2601) new cancer cases would have been prevented. Conclusions: Alcohol consumption in France appears to cause almost 8% of new cancer cases, with light and moderate drinking contributing appreciably to this burden. A 10% drop in drinking in France would have prevented more than 2000 (estimated) new cancer cases in 2015.